PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN JENIS WACANA NARASI - Sopia Rahmalia; Rohani Rohani (Institut Pendidikan Indonesia Garut, 2020)
This study was conducted to determine the effect of cooperative learning model Think Talk Write (TTW) in the learning of reading comprehension types of narrative discourse. This study, entitled